MENINGOENCEPHALITIS DUE TO VARICELLA ZOSTER VIRUS IN AIDS PATIENTS. REPORT OF ELEVEN CASES AND REVIEW OF THE LITERATURE - CORTI, Marcelo; VILLAFAÑE, María F.; VITTAR, Natalia; BANCO, María C.; PRIARONE, Maia; MAMMANA, Lilia; GILARDI, Leonardo (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
Neurological complications of varicella-zoster virus (VZV) are infrequent and include various clinical pictures. The reactivation of VZV in patients with AIDS is generally associated with an acute and severe meningoencephalitis. We report the epidemiological, clinical and virological data from 11 consecutive patients with diagnosis of HIV/AIDS and central nervous system (CNS) involvement due to VZV. All patients were male and seropositive for HIV. The primary risk factor for HIV infection was unprotected sexual contact. The median of CD4 T cell count was 142 cells/µL. All of them presented signs and symptoms of meningoencephalitis. Six patients (54.5%) presented pleocytosis; they all showed high CSF protein concentrations with a median of 2.1 g/dL. Polymerase chain reaction of cerebrospinal fluid specimen was positive for VZV in all of them and they were treated with intravenous acyclovir at doses of 30/mg/kg/day for 21 days. Overall survival was 63% (7 of 11 patients). The four dead patients had low cellular counts in CSF, below the median of this parameter. VZV should be included among the opportunistic pathogens that can involve CNS with a diffuse and severe meningoencephalitis in patients with advanced HIV/AIDS disease.